Physical mechanisms for soil moisture effects on microbial carbon-use efficiency in a sandy loam soil in the western United States. (November 2020) - Butcher, Kirsten R.; Nasto, Megan K.; Norton, Jeanette M.; Stark, John M.
Abstract: Microbial carbon-use efficiency (CUE) is defined as the portion of carbon (C) incorporated into biomass relative to the total carbon consumed and plays a pivotal role in regulating microbially-mediated C and nutrient transformations in soil. However, little is understood about how CUE is impacted by edaphic properties, like soil moisture. Soil moisture physically regulates microbial activity through its effects on both water potential and water content. Low water potential can result in high, compensatory intracellular solute concentrations that may inhibit biochemical functions through cytoplasmic desiccation, whereas low soil water content results in thin water films that can limit substrate diffusion, reducing microbial access to dissolved substrates. Because these two aspects of soil moisture may affect microbial respiration differently than C assimilation, they may have different effects on CUE. The purpose of this research was to evaluate the relative importance of water potential and water content in regulating CUE of soil microbial communities. Moist soil incubations of a sandy loam soil were used to determine the impact of both aspects of soil moisture on CUE, and soil slurries were used to determine the impact of water potential alone. Both 13 C-acetate and 15 N-ammonium were added to moist soils and slurries to quantify gross rates of C and N transformations. In moist soils, acetate assimilation and respiration rates and gross N mineralization and immobilization rates increased exponentially with increasing soil moisture (−3.0 to −0.03 MPa). In contrast, acetate assimilation and respiration and gross N transformation rates remained constant in soil slurries across a similar water potential gradient, created by modifying solute concentrations. Similarly, values of CUE in moist soils increased exponentially with increasing soil moisture, whereas slurry values of CUE remained constant across the soil water potential gradient. Because no changes in rates and CUE were observed in slurries, changes observed in moist soils were attributed to limited substrate diffusion associated with low water contents rather than to adverse physiological effects associated with low water potentials. Results of this study demonstrate that limited substrate diffusion is the primary physical mechanism through which soil moisture regulates microbially-mediated C and N transformation rates and CUE in this sandy loam soil. Highlights: Mechanistic effects of soil moisture on CUE evaluated. Water content regulated CUE in a sandy loam soil. No effect of water potential per se on CUE in a sandy loam soil. Water content alone may be a sufficient predictor of microbial activity.